Elektroninės komercijos apmokestinimas pridėtinės vertės mokesčiu - Rotomskis, Irmantas; Štitilis, Darius (Information & Media, 2008)
Straipsnyje nagrinėjama elektroninės komercijos ir pridėtinės vertės mokesčio suderinamumo dilema. Daugiausia dėmesio skiriama naujai sukurtai ir nuo 2004 m. gegužės 1 d. Lietuvoje įsigaliojusiai apmokestinimo schemai, kuri taikoma specialiai elektroniniu būdu teikiamoms paslaugoms. Pardavėjams, užsiimantiems elektronine komercija, keliami dideli reikalavimai, todėl pabrėžiama, kad pareigos, kurias įtvirtina teisės normos, neatitinka galimybių, kurias suteikia informacinės technologijos. Net ir nauji pridėtinės vertės mokesčio pokyčiai ne iki galo suderino mokesčių institucijų ir elektronine komercija užsiimančių pardavėjų tarpusavio santykius. Naujoji schema – tai tik pirmas, tačiau reikšmingas žingsnis siekiant tradicinį pridėtinės vertės mokestį efektyviai pritaikyti naujai komercijos formai.Value added tax in electronic commerceIrmantas Rotomskis, Darius ŠtitilisSummaryElectronic space is steadily gaining popularity as an attractive environment for business organisation. Electronic dispatch of goods in a digital form allowing to avoid traditional checking procedure, increased level of anonymity of operations carried out within internet, introduction of electronic currency, and considerable mobility of electronic commerce account for the governmental institutions’ concern about effective application of tax rates that have existed up until now. Special attention is given to the value added tax (VAT) as its regulation by current legislation has become largely ineffective in terms of newly-introduced business models.Criticism of VAT for its poor effectivity in the area of electronic commerce was based, to a degree, on the circumstance that identification of the second party of a deed, that is the buyer, was impossible. Most authors argue that information technologies allow to identify only the IP of a computer system, not a subject who used it. The main objective of this article is to analyse the dilemma of e-commerce and value added tax (VAT) compatibility. A search for effective ways of imposing a VAT tax on electronic commerce lasted in the European Union up till 2000. In 2002, the adoption of the Sixth Directive “On Value Added Tax” consolidated a new pattern applied to the taxation of services rendered exclusively in an electronic way. Requirements of this Directive are in force also in the Republic of Lithuania since 1 May 2004.High demands are raised to the e-commerce sellers, therefore the focus is set on inadequateness between obligations which are definite in legal norms and opportunities which e-commerce provides. Even the new changes applying VAT does not wholly balance the relationship between tax institutions and e-commerce sellers. The new scheme is a first step to the efficient application of traditional VAT to the new form of commerce.